19F NMR Relaxometry and Diffusometry for Measuring Cargo Molecule Dynamics in GelMA Hydrogels - Chun‐Wei Chang; Bronwin L. Dargaville; Konstantin I. Momot; Dietmar W. Hutmacher (Macromolecular Materials and Engineering)
Abstract Understanding payload diffusion is an important topic in hydrogel drug delivery. While proton nuclear magnetic resonance (NMR) spectroscopy allows for direct examination of water dynamics in hydrogels, it is challenging to study the dynamics of payloads due to spectral crowding and distortions. Fluorine‐19, not biologically endogenous in humans and having high NMR receptivity, can be easily incorporated into molecules of interest and therefore used as an alternative probe for dynamics of payload molecules in hydrogels. In this study, the dynamics of fluorine‐containing compounds trifluoroethylamine (TFEA, a small molecule), ciprofloxacin (CF, a medium‐size molecule), and fluorinated lysozyme (FL, a ≈15 kDa protein) are measured both in solution and gelatin methacrylate (GelMA) hydrogels. For each payload molecule, the rotational correlation time and translational diffusion coefficient, as well as the effective microviscosity of the media, are measured. Spin‐spin relaxation (T2) is also used to probe chemical exchange as an indicator of payload–polymer interactions. The in situ interaction between payload and polymer network and precise characterization of payload dynamics within hydrogels show that fluorine‐19 nuclear magnetic resonance (19F NMR) relaxometry and diffusometry are important techniques in hydrogel drug delivery and, more generally, in biomaterial science, tissue engineering, and regenerative medicine.